La laïcité à Mayotte. Un cas d'école - Hugo Bréant (Les éditions de la Maison des sciences de l'Homme, 2022)
The territory of Mayotte was early excluded from the application of the law of separation of Church and State in 1905. A century later, the law prohibiting the wearing of religious signs in public schools thus became the cornerstone of a secular policy in the 101st French department. This article aims to understand the implementation of this model of a public and secular school in a department where the majority of students are Muslim and attend the Koranic school in parallel. The legislative debates highlighted the specificities of the context of Mayotte and established a clear demarcation between a problematic religious veil and a tolerated cultural veil. An analysis of pedagogical and disciplinary practices, carried out by directors in their school and by teachers in their classrooms, demonstrates the fluidity of this border. The management of secularism in action is marked by constant accommodation.